Estudo da hidrodesoxigenação do guaiacol em fase vapor sobre catalisadores de platina suportados em matrizes à base de nióbio: xNb2O5/(100-x)Al2O3 (x = 0, 5, 20, 100, % peso) e NbOPO4 - Silva, Nathacha Kare Gonçalves (2018)
Problems arising from fossil fuels combustion, such as local air pollution, the global climate change, and the conflicts between countries for finite fossil reserves stimulated the pursuit for renewable sources of energy. Lignocellusic biomass has the potential to be transformed in fuels, fuels additives, and sustainable chemicals in the perspective of non-competition with food production. The raw product thermochemically treated by fast pyrolysis of lignocellulosic biomass shows undesired properties derived from the high oxygen content and needs to be upgraded, in an analogue way as occurs with crude petroleum. Hydrodeoxygenation (HDO) is one of the processes that can be applied to upgrade the non-condensed or condensed (bio-oil) pyrolysis vapors. In this work, the HDO of guaiacol (2-methoxyphenol, C7H8O2), model compound representative of the lignin portion of biomass, was evaluated to function as foundation for the development of more complex studies. Initially, a thermodynamic analysis of the guaiacol conversion was carried out using the software UniSim Design R400. The results of the chemical equilibrium revealed that most of the reactions were exothermic and that the HDO of guaiacol did not show thermodynamic restriction to occur. The experimental part of this study involved the guaiacol reaction with hydrogen at atmospheric pressure using niobium-based catalysts. The catalytic system tested was comprised by platinum supported on niobium oxide (Nb2O5), alumina (Al2O3), niobia-alumina (5%Nb2O5/Al2O3; 20%Nb2O5/Al2O3), and niobium phosphate (NbOPO4). The catalysts were characterized by X-ray diffraction (XRD), nitrogen physisorption, CO chemisorption, and temperature-programmed desorption of isopropylamine. The influence of operating conditions such as hydrogen partial pressure, temperature, and space velocity on both activity and selectivity were analyzed. It was observed that the higher the niobia loading in the niobia-alumina mixed support the higher was the selectivity for phenol. The Pt/NbOPO4 catalyst formed less deoxygenated products than Pt/Nb2O5. Pt/Nb2O5 prepared using ammonium niobium oxalate as precursor was superior to the catalyst prepared using niobic acid. The Pt/Nb2O5 was the best performance catalyst, which was attributed to the interaction between Pt and NbOx species (metal-support interface).